DeepSeek-R1 Reinforcement Learning Fine-Tuning and Mathematical Reasoning Benchmark Performance - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: What is the impact of DeepSeek-R1's reinforcement learning fine-tuning on mathematical reasoning benchmarks relative to supervised fine-tuned baselines of similar parameter count. 12 claims were extracted from source literature; 2 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 4.5/10. This report is a machine-genera
Machine-generated literature synthesis.